Comparing efficacy and adherence of smartphone-guided exercises to conventional self-directed exercises for neck pain in office workers: A randomized controlled trial protocol - Sana Salah; Anis Jellad; Manel Mili; Amr Chaabeni; Mohamed Hédi Bedoui; Helmi Ben Saad (PLoS ONE, 2025)
Background Self-exercises focusing on strength and endurance training, as well as self-mobilization, are effective in neck pain (NP). This study aims to investigate the differences in self-management using two workplace-based interventions: a smartphone application consisting of personalized neck exercises compared to conventional approach (self-exercises program on paper) in chronic NP office workers. Methods The project is a prospective, superiority, randomized controlled trial. Fifty participants with chronic NP will be randomly assigned into the interventional group (IG, n = 25), utilizing the smartphone application, or the control group (CG, n = 25). The CG includes the use of a paper sheet with exercises and recommendations, and the IG includes the use of a smartphone application, which provides individualized exercise programs. Both protocols will last three months and will be preceded by an educational session at baseline for all participants. The main outcome measure comprises pain intensity evaluated according to the pain intensity number rating scale. Secondary outcomes are function evaluated according to the neck disability index, quality of life according to the short form 12, and participants’ adherence to self-exercises. Outcome measures will be collected at baseline, and one and three months of follow-up. Discussion The current project will evaluate the effectiveness of a smartphone application consisting of personalized neck exercises, when compared with a conventional approach for self-rehabilitation. The smartphone application will allow to monitor the participants’ status and to help resolving the problem of adherence to self-exercises in chronic NP. Despite some limitations may be related to the short follow-up duration, the study findings could help to develop evidence-based knowledge about the impact of workplace interventions using new technologies in mitigating discomfort and promoting well-being among affected workers. Trial Registration ClinicalTrials.gov. NCT06485804 Registered on July 1, 2024.